Thermal and Environmental Degradation of Low-Voltage Cable Insulation for Predictive Maintenance Applications - Dekki Sandi Nugraha; Dwi Agus Riyanto (BRIDGE : The Multidisciplinary Research Portal, 2025)
Low-voltage cable insulation degradation poses a significant risk to the reliability and safety of power distribution systems, particularly under combined thermal and environmental stress conditions. This study investigates the dominant degradation mechanisms affecting low-voltage cable insulation in distribution networks, using field measurements at the PR009 transformer substation as a representative case. The analysis focuses on the interaction between thermal overloading, electrical stress, moisture ingress, and environmental contamination, and their cumulative impact on insulation performance. A quantitative experimental field approach was employed, integrating insulation resistance testing, dielectric loss (tan δ) analysis, partial discharge evaluation, and theoretical modeling of electrical and thermal behavior. The results indicate that excessive current loading and phase imbalance lead to elevated conductor temperatures, intensifying thermal stress and accelerating insulation aging. Intrinsic electrical breakdown, streamer-induced partial discharge activity, dielectric losses, and limited heat dissipation were identified as primary contributors to degradation. Environmental factors, particularly high humidity and acidic soil conditions, were found to further exacerbate chemical and mechanical deterioration of polymeric insulation materials. The findings highlight the effectiveness of condition-based diagnostic techniques for early detection of insulation deterioration and support the implementation of predictive maintenance strategies. This study provides practical insights for utilities and asset managers to enhance service reliability, reduce unplanned outages, and optimize the lifecycle management of low-voltage distribution cables under realistic operating and environmental conditions.